Predicting Psychological Hardiness Based on Self-Regulation and Stress Coping Strategies - Maryam Zahiri; Katrin Vaziri (Iranian Journal of Educational Research)
Objective: The current investigation was carried out in order to explore the anticipation of psychological hardiness based on the elements of self-regulation of emotions and stress coping strategies. Methods: The population under examination in this particular study encompassed all female individuals who sought assistance at the Health House located in the 6th precinct of Tehran during the 2023. A total of 80 female participants seeking aid at the health facility in the 6th district of Tehran were included in the sample, selected through purposive sampling techniques. The data collection instruments employed in this study were the stress coping strategies questionnaire developed by Lazarus and Folkman (1998), Cognitive Emotion Regulation Questionnaire (CERQ) developed by Garnefski and Kraaij (2007) and Kobasa et al. hardiness questionnaire (1985). The analysis of the research data involved the utilization of Pearson's correlation coefficient and the multivariate regression technique. Results: The outcomes of the study suggest that the components of emotional self-regulation and stress coping strategies have the ability to predict psychological hardiness (p < 0.05). Conclusions: Based on the outcomes derived from the study, it is plausible to infer that the components related to emotional self-regulation in conjunction with stress coping mechanisms serve as reliable predictors of an individual's psychological hardiness.